(untitled) (Bangladesh Journal of Botany, 2019)
For optimization of cultural conditions for algal biomass production of two local filamentous freshwater algae, namely Hydrodictyon reticulatum, and Spirogyra communis were cultured. Among all these tested media, H. reticulattum gave maximum biomass (18.6 g/l) in Bristol medium whereas, S. communis gave the biomass of 10.5 g/l in Bristol soil media. Then the effect of different carbon sources (lactose, glucose, cellulose and starch) supplement in Bristol media was evaluated for biomass production. Among all the sources cellulose at 1 g/l was found to be significant for optimal mass production of (15.81 g/l) and (18.6 g/l) of S. communis and H. reticulatum, respectively. Both the algal species gave insignificant results in all other carbon sources. The effect of different nitrogen sources (ammonium nitrate, ammonium sulphate, ammonium chloride, potassium nitrate and urea) was tested for biomass production. Urea at 0.1 g/l was found to be best (20.7 g/1000 ml) for optimal growth of H. reticulatum as compared to (16.86 g/1000 ml) of S. communis. However, cellulose as carbon source and urea as nitrogen source were optimized for significant growth of both the algal species. The comparison between the growth rates of both specimens was evaluated. Both the species gave maximum growth up to 15 days of incubation and then the growth started decreasing gradually. It is indicated that the volumetric growth of H. reticulatum is significant in the selected media as compared to S. communis.